PERGESERAN MAKNA ESENSI PERNIKAHAN DI KECAMATAN PEDAMARAN KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN – STUDI KASUS SOSIOLOGI HUKUM KELUARGA - Nurmala HAK; Yusdani Yusdani; Januariansyah Arfaizar (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract: At this time the implementation of Walimatul’urs has undergone a change or a shift that is almost out of the goal of the Walimatul’urs itself, it has become a common culture that what is called a wedding party or Walimatul’urs must be luxurious, starting from giving dowries and holding large parties and so on. This is what happened in the community of Pedamaran District, Ogan Komering Ilir Regency. How is the Walimatul’urs Pattern in Pedamaran District, Ogan Komering Ilir Regency, what are the faktors that cause a shift in the meaning of the essence of Walimatulurs in Pedamaran District, Ogan Komering Ilir Regency and How is the Review of Islamic Law on the shift the meaning of the essence of Walimatul’urs in Pedamaran District, Ogan Komering Ilir Regency and this research is classified as field research. Sources of data used are primary and secondary data sources. Data collection techniques in this study using interviews, documentation and observation. The result is, it was concluded that the initial goal of the people of Pedamaran District, Ogan Komering Ilir Regency in Walimatul’urs was very good, namely to please children and to entertain invited guests and as an expression of gratitude, but in its implementation it has experienced a shift and the resulting impact is social jealousy between communities, used to obtain profit (business), the presence of prestige, disturbing the peace caused by people who drink liquor and entertainment that lasts until late at night Keywords: Walimatul'urs, Sociology, Family Law.